2019
DOI: 10.3390/molecules24193532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Chemical Composition of Free-Terpene Hydrocarbons Essential Oils on Antifungal Activity

Abstract: In this study, Carum carvi L. essential oil (CEO) and Origanum majorana L. essential oil (MEO) was steam-distillated under reduced pressure. We henceforth obtained three fractions for each essential oil: CF1, CF2, CF3, MF1, MF2, and MF3. Then, these fractions were characterized using the gas chromatography–mass spectrometry (GC-MS) technique. The results indicated that some fractions were rich in oxygenated compounds (i.e., CF2, CF3, MF2, and MF3) with concentrations ranging from 79.21% to 98.56%. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…The oxygenated hydrocarbon composition is higher in C. lemon and C. aurantifolia , with percentages of 33.53% and 14.59%, respectively. High concentrations of oxygenated hydrocarbons in C. lemon and C. aurantifolia could be attributed to the strong antifungal activities of these oils [ 21 ]. They could synergistically increase the effect of limonene and other monoterpene hydrocarbons [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The oxygenated hydrocarbon composition is higher in C. lemon and C. aurantifolia , with percentages of 33.53% and 14.59%, respectively. High concentrations of oxygenated hydrocarbons in C. lemon and C. aurantifolia could be attributed to the strong antifungal activities of these oils [ 21 ]. They could synergistically increase the effect of limonene and other monoterpene hydrocarbons [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The GC analysis showed an increase in the proportion of oxygenated compounds in caraway fractions in comparison to hydrocarbons, therefore, caraway oil could be considered to be highly oxygenated while clove oil is moderately oxygenated. Previously, oxygenated compounds have been reported to have bioactive inhibitory effects against several fungal strains, including numerous Penicillium strains, such activity of the oil could be attributed to the oxygenated carvone that possessed higher antifungal activity, as well as antioxidant activity [ 40 , 41 , 42 ]. Such compounds could also inhibit the rate of primary and the secondary oxidation product formation.…”
Section: Discussionmentioning
confidence: 99%
“…Such compounds could also inhibit the rate of primary and the secondary oxidation product formation. Furthermore, the physical nature of the rich oxygenated essential oils, for example, their low molecular weight combined with a lipophilic character, allow them to penetrate the cell membrane more quickly compared to other substances [ 41 , 43 ]. Clove oil also showed good potential in inhibiting the growth of Penicillium polonium .…”
Section: Discussionmentioning
confidence: 99%
“…Carum carvi EO contains rich oxygenated compounds, such as carvone and limonene, affecting the integrity of the fungal cell membrane. It has been shown that free-terpene hydrocarbons containing oxygenated compounds with low molecular weights are able to penetrate through the cell membrane after combining with lipophilic molecules [ 36 ]. Furthermore, phenolic compounds with OH group and aromatic structure have been identified to contribute to the deactivation of fungal enzymes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that free-terpene hydrocarbons containing oxygenated compounds with low molecular weights are able to penetrate through the cell membrane after combining with lipophilic molecules [ 36 ]. Furthermore, phenolic compounds with OH group and aromatic structure have been identified to contribute to the deactivation of fungal enzymes [ 36 ]. Our findings revealed that C. carvi EO could successfully inhibit extracellular proteinase and phospholipase activities in C. albicans .…”
Section: Discussionmentioning
confidence: 99%